1989
DOI: 10.1210/mend-3-7-1037
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Thyrotroph-Specific Factors andCis-Acting Sequences of the Murine Thyrotropinβ Subunit Gene

Abstract: Pituitary thyrotroph cells specialize in the synthesis of TSH, and thus represent a model to study cell-specific gene expression. We have used the murine TSH beta (mTSH beta) gene promoter and TSH-producing and nonproducing transplantable tumors derived from murine thyrotroph cells, referred to as TtT-97 and MGH 101A, respectively, to identify nuclear factors which selectively interact with the mTSH beta gene. DNase I protection analyses demonstrate that factors present in TtT-97 nuclear extracts bind with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The con¬ trasting patterns of basal expression of the human a promoter in pituitary and choriocarcinoma cells suggest that pituitary cell-specific trans-acting factors may exert both stimulatory and inhibitory actions on 5' flanking a elements in such pituitary cells. This hypothesis is supported by description of thyrotroph-specific factors which bind to regions of the murine TSH-ß gene required for optimal TSH-ß expression (Alexander, Gordon, Wood et al 1989) and of multiple overlapping protein-binding sites in human a 5'flanking DNA (Jameson et al, 1988), includ¬ ing those shown to be important functionally in the present studies.…”
Section: Discussionsupporting
confidence: 70%
“…The con¬ trasting patterns of basal expression of the human a promoter in pituitary and choriocarcinoma cells suggest that pituitary cell-specific trans-acting factors may exert both stimulatory and inhibitory actions on 5' flanking a elements in such pituitary cells. This hypothesis is supported by description of thyrotroph-specific factors which bind to regions of the murine TSH-ß gene required for optimal TSH-ß expression (Alexander, Gordon, Wood et al 1989) and of multiple overlapping protein-binding sites in human a 5'flanking DNA (Jameson et al, 1988), includ¬ ing those shown to be important functionally in the present studies.…”
Section: Discussionsupporting
confidence: 70%
“…Within this broad area, four DNase I protected regions have been identified using nuclear extracts from TSH␤ expressing mouse TtT-97 thyrotropic tumor cells (7)(8)(9). These have been termed D1 (Ϫ253 to Ϫ222), D2 (Ϫ196 to Ϫ176), P1 (Ϫ133 to Ϫ88), and P2 (Ϫ86 to Ϫ64).…”
mentioning
confidence: 99%
“…1). The trimerized poly(A) stops upstream of the polylinker and luciferase reporter gene in pA3Luc result in a promoterless reporter vector with negligible activity in gene transfer studies, and thus the activity of any promoter fragment cloned into the polylinker can be assayed with increased sensitivity owing to the lack of significant contribution from vector readthrough (3,4,42,68). The orientation of the inserted promoter fragment and documentation of specific rPRL promoter mutations in either the pA3Luc-or the pGEM4-based vectors were verified by DNA sequencing using a luciferase oligonucleotide primer as previously reported (3,4,68).…”
mentioning
confidence: 99%
“…Following electroporation, cells were maintained in culture for 8 to 24 h, depending on the optimal time of luciferase expression for each cell line (30). Cells were then harvested and lysates were measured for luciferase activity as previously reported (3,12,30,31,68 (39,40,53,57). While significant reduction in promoter activity could be due to removal of a critical positive transcription element, such as FPIII, the almost complete loss of promoter activity with the -127 deletion suggested to us that this 5' deletion endpoint unmasked a strong repressor element.…”
mentioning
confidence: 99%